Elymus multiramosus (Poaceae), a new species from the north-western Qinghai-Tibetan Plateau, China - Yong-Chao Zhang; Xiao-Xing Wei; Yan Qin; Yong Liu; Shu-Zhen Zhang; Zhi-Feng Jia; Wen-Hui Liu (PhytoKeys)
A new species from China, Elymus multiramosus Y.C. Zhang, sp. nov. is described and illustrated herein, based on morphological characters and molecular phylogenetic analysis. The taxonomic descriptions of E. multiramosus and the comparison with related species are presented. The taxonomic distinctiveness of this new species was inferred by Maximum Likelihood (ML) analysis and Bayesian phylogenetic analysis, based on the complete chloroplast genome sequence. It is assigned to the Elymus section and bears similarity to Elymus nutans Griseb. However, it can be easily distinguished from other species by its compound spike, in contrast to the simple spike inflorescence typical of those species. The compound spike is characterised by rhachillas that are extended at the base of the main axis, giving rise to 3–6 mini-spike-like branches. Notably, these branches significantly increase in length from the top towards the bottom of the compound spike. In the molecular phylogeny, Elymus multiramosus from Qinghai, north-western China, is phylogenetically positioned as a distinct lineage. The lineage comprising Elymus sinosubmuticus from Sichuan, east of the Tibetan Plateau and Elymus nutans from the Himalayas forms a sister group to Elymus multiramosus, suggesting that these three species share a common ancestor that is distinct from the lineage leading to Elymus atratus from Gansu, north of the Tibetan Plateau.